2012
DOI: 10.1590/s0100-204x2012001200006
|View full text |Cite
|
Sign up to set email alerts
|

Fenologia e produção de cultivares de framboeseiras em regiões subtropicais no Brasil

Abstract: O objetivo deste trabalho foi avaliar a fenologia e a produção de cultivares de framboeseiras em condições subtropicais, no Brasil. O experimento foi realizado nos municípios de Lavras, MG, e Marechal Cândido Rondon, PR. Foram avaliadas sete cultivares, com as espécies Rubus idaeus (vermelhas, 'Heritage', 'Polana', 'Autumn Bliss' e 'Batum'; e amarelas, 'Golden Bliss', em Lavras, e 'Fall Gold', em Marechal Cândido Rondon) e R. niveus (framboesa-negra), além de um híbrido (Boysenberry) entre R. idaeus e amora-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 19 publications
3
12
0
4
Order By: Relevance
“…It is highly related to weight. These results agree with those reported by Moura et al (2012), who found that Black Raspberry and Heritage cvs had low fresh weight average (2.1 and 2.6 g, respectively), and Boysenberry hybrid grown in Minas Gerais (Brazil) registered 5.3 g. It seems most likely that these slight differences are due to the different cultivation techniques, and/or soil and weather conditions, which may slightly change the quality parameters.…”
Section: Fresh Weightsupporting
confidence: 91%
“…It is highly related to weight. These results agree with those reported by Moura et al (2012), who found that Black Raspberry and Heritage cvs had low fresh weight average (2.1 and 2.6 g, respectively), and Boysenberry hybrid grown in Minas Gerais (Brazil) registered 5.3 g. It seems most likely that these slight differences are due to the different cultivation techniques, and/or soil and weather conditions, which may slightly change the quality parameters.…”
Section: Fresh Weightsupporting
confidence: 91%
“…Há desconfiança de que se trate da cultivar 'Autumn Britten', que, no Brasil, tenha recebido, pelos produtores, o nome 'Britten' e, posteriormente, 'Batum' (RASEIRA et al, 2004). Ela apresenta produtividade estimada de 5t/ha, no primeiro ano pós-plantio (MOURA et al, 2012). Nessa região, as framboeseiras, que são menos exigentes em frio (250 horas), podem apresentar como vantagem a antecipação da colheita em relação a alguns estados da região sul do Brasil.…”
Section: Indroduçãounclassified
“…Estacas radiculares, obtidas fragmentando as raízes das hastes que brotam nas entrelinhas, também são usadas na produção de mudas desta fruteira (MARO et al, 2012;MOURA et al, 2012).…”
Section: Indroduçãounclassified
“…Large part of its culture practices is carried out based on the tomato plant cultivation (LIMA et al, 2009;IANCKIEVICZ et al, 2013). Physalis peruviana L. has a potential to be produced in subtropical areas, similarly to small fruits like blackberries and raspberries, since there are similarities in their climatic demands and cultivation techniques such as farming practices and harvesting (MOURA et al, 2012, TIBERTI et al, 2015.…”
Section: Introductionmentioning
confidence: 99%